Pemberdayaan Masyarakat Melalui Pengembangan Sektor Wisata: (Studi di Desa Pujon Kidul Kecamatan Pujon Kabupaten Malang) - Nasyah, Ella Zuhrotin (Publiciana, 2022)
The tourism sector is one of the most crucial categories that can support the community's economy and also support the country. In recent years, the tourism sector has been increasingly developed by various regions in Indonesia, especially in rural areas, one of which is the Pujon Kidul, Malang. The purpose of this research is to find out how the tourism industry can help empower local communities in Pujon Kidul Malang and to find out the socio-economic conditions of the community from before and after the development of the tourism sector. The research method used in this research is a descriptive qualitative research method. The data obtained in the form of primary data obtained through direct observation and interviews with research informants, as well as secondary data obtained through books, journals and documents related to the research topic. The sampling technique used by the researcher is a purposive sampling technique to take samples with certain considerations. The results showed that after the development of the tourism sector, there was an extraordinary development in Pujon Kidul. The community is empowered through the availability of UKM and UMKM as well as the availability of job opportunities through tourism. In addition, the development of the tourism sector in Pujon Kidul Village has brought a significant difference to the socio-economic conditions of the community before and after the development of the tourism sector.